Models based on nucleic acid methylation regulators will contribute to facilitating cancer precision medicine - Zhang, Wen (BMC medicine, 2021)
Background With the development of molecular biology techniques, it is possible to explore the tumorigenesis and cancer development mechanisms and intrinsic characteristics of single cancer types from the perspectives of chromosome, genome, transcriptome, protein expression, and epigenetics, and on this basis, molecular subtypes can be classified [1, 2]. [...]the 5mC score was significantly related to the cancer stemness and could reflect TME heterogeneity. Usually, a higher cancer stemness indicates a decrease in anti-cancer immunity and lower ICB response. [...]the 5mC score could effectively stratify the immune phenotypes of BLCA.